Simulation-Based Optimization for the Operation of Toll Plaza at Car Park Exit with Mixed Types of Tollbooths and Waiting-Time-Dependent Service - Shanchuan Yu; Yuchuan Du; Jindong Wang; Yishun Li; Yong Zhu (Journal of Advanced Transportation)
This study presents an approach of simulation-based optimization to the operation of the toll plaza at the car park exit. We first propose a simulation model, as the representation of the queueing system for the toll plaza with mixed-type customers and servers where the service time is dependent on the waiting time of customer. Then, a simulation-based integer programming model is developed to design more traffic-efficient yet cost-effective operation schemes. It is decomposed by a rolling horizon approach into subproblems which are all solved via the Kriging metamodel algorithm. A numerical example is presented to illustrate the model and offer insight on how to achieve traffic efficiency and cost-effectiveness.